Digitalization, Banking Performance, and Sharia Supervisory Board Efficiency: Evidence from Indonesian Islamic Commercial Banks - Meliana, Rini; Puspita, Meliana Dwi; Diana, Azka Nur; Qur'an, Amanah Aida; Mawardi, Mawardi (MALIA: Journal of Islamic Banking and Finance, 2026)
The massive digital transformation in the Islamic banking industry has fundamentally changed the operational and supervisory landscape of Islamic banking. Furthermore, Islamic banking performance, measured through financial indicators and Islamic compliance, is a crucial factor in determining the complexity of supervision required by the SSB. The efficiency of SSB is crucial given its role as the guardian of the enforcement of Islamic principles in every bank product and operation. This study aims to examine and analyze the influence of digitalization and Islamic banking performance (bank size, leverage, bank age, and profitability) on the efficiency of SSB. Digitalization is operationalized using a text-mining approach applied to bank annual reports, while SSB efficiency is measured through a disclosure score derived from the content of SSB reports. Using a quantitative approach, this research investigates how digitalization and banking performance influence SSB efficiency. Panel data regression via EViews 25 was employed to analyze 40 sampled Islamic commercial banks registered with the OJK during 2019–2024. The results indicate that digitalization, bank size, leverage, and profitability do not significantly on the efficiency of the SSB. However, bank age significantly influences the efficiency of the SSB. Simultaneously, digitalization, bank size, leverage, bank age, and profitability significantly on the efficiency of SSB. Practically, these findings suggest that Islamic banks should prioritize the accumulation of institutional experience and the strengthening of SSB member competence over reliance on digital infrastructure alone when designing sharia supervision mechanisms.